Extinction : a novel [compact disc, unabridged] - Preston, Douglas J. (Macmillan Audio, 2024)
Erebus Resort, occupying a magnificent, hundred-thousand acre valley deep in the Colorado Rockies, offers guests the experience of viewing woolly mammoths, Irish Elk, and giant ground sloths in their native habitat, brought back from extinction through the magic of genetic manipulation. When a billionaire's son and his new wife are kidnapped and murdered in the Erebus back country by what is assumed to be a gang of eco-terrorists, Colorado Bureau of Investigation Agent Frances Cash partners with county sheriff James Colcord to track down the perpetrators. As killings mount and the valley is evacuated, Cash and Colcord must confront an ancient, intelligent, and malevolent presence at Erebus, bent not on resurrection, but extinction.